Semiotics Analysis Of The Meaning Of Power In The Song “2+2=5” By Radiohead - Muhammad Muchalif; Muhammad Alfikri (IHSA Institute, 2022)
Using Roland Barthes' semiotic theory, this study investigates the meaning of power in the lyrics of Radiohead's song